(untitled) (Community Based Medical Journal, 2013)
Escherichia coli (E. coli) is an important group of pathogens associated with diarrhea among children. Despite the fact that diarrhaegenic Escherichia coli (DEC) has been identified as a major etiologic agent of childhood diarrhea, only a few studies have been performed in Bangladesh to identify these organisms. The objective of this study was to determine the frequency and antimicrobial susceptibility of DEC obtained from patients with acute diarrhea. To detect DEC in patients with acute diarrhea, a total of 300 stool specimens were tested by multiplex polymerase chain reaction (PCR). The antimicrobial susceptibility of DEC were tested by Kirby-Bauer disc diffusion technique as per recommendation of CLSI (Clinical and Laboratory Standards Institute), 2010. Out of 300 stool specimens collected from patients with acute diarrhea, the DEC was detected in 18% (54/300) cases. The dominating strain was Enterotoxigenic E. coli ( ETEC) (13%, 39/300), followed by Enteroaggregative E. coli (EAEC) (5%, 15/300) and no Enterohemorrhagic E. coli (EHEC), Enteroinvasive E. coli ( EIEC) and Enteropathogenic E. coli ( EPEC) could be detected. Detected ETEC were 100% sensitive to Ceftriaxone, Nitrofurantioin, Amikacin, 94% sensitive to Nalidixic acid, 89% sensitive to Gentamycin, 83% sensitive to Ciprofloxacin, 79% sensitive to Cephalexin, 39% sensitive to Amoxycillin, 46% sensitive to Tetracyclin and 31% sensitive to Cotrimoxazole. Detected EAEC were 100% sensitive to Ceftriaxone, Nitrofurantioin, Amikacin, Nalidixic acid, 90% sensitive to Gentamycin and Ciprofloxacin, 85% sensitive to Cephalexin, 41% sensitive to Amoxycillin, 49% sensitive to Tetracycline and 31% sensitive to Cotrimoxazole. Both ETEC and EAEC isolates exhibited decreased susceptibility for Amoxycillin, Tetracycline and Cotrimoxazole. Our results revealed that ETEC and EAEC, had significant association with acute diarrhea and should be considered as potential pathogens. Guidelines for appropriate use of antibiotics in tertiary care hospitals need updating. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16698 Community Based Medical Journal 2013 July: Vol.02 No 02: 46-51